Clinical analysis of human umbilical cord mesenchymal stem cell allotransplantation in patients with premature ovarian insufficiency. (29th October 2020) - Yan, Long; Wu, Yixuan; Li, Li; Wu, Jun; Zhao, Feiyan; Gao, Zheng; Liu, Wenjing; Li, Tianda; Fan, Yong; Hao, Jie; Liu, Jianqiao; Wang, Hongmei
Abstract: Objective: Premature ovarian insufficiency (POI) is a refractory disease that seriously affects female fertility. Growing body of evidence has indicated mesenchymal stem cells (MSCs) as promising resources in regenerative medicine. In this study, we treated POI patients with umbilical cord‐derived MSCs (UCMSCs) and then investigated the restoration of ovarian function and clinical outcomes through follow‐ups. Materials and methods: Sixty‐one patients diagnosed with POI participated in this study. UCMSCs were isolated and cultured according to GMP standards, and then transplanted to the patients' ovary by orthotopic injection under the guidance of vaginal ultrasound. We monitored side effects, vital signs and changes in clinical and collected haematological and imaging parameters during the follow‐ups. Results: All patients showed normal clinical behaviour without serious side effects or complications relevant to the treatment. Transplantation of UCMSCs rescued the ovarian function of POI patients, as indicated by increased follicular development and improved egg collection. POI patients who experienced shorter amenorrhoea durations (<1 year) seemed to obtain mature follicles more easily after stem cell therapy, and patients with better ovarian conditions (pre‐operative antral follicles) were more likely to derive the better outcomes by UCMSC injection. Four successful clinical deliveries were obtained from POI patients after UCMSC transplantation, and all of these babies are developed normally. Conclusions: The clinical trial result sugggests a possible therapy for POI by UCMSC transplantation. Abstract : 82 participants diagnosed of POI were screened for this study, 20 of them were ineligible as failure to meet the inclusion criteria, 1 patient declined. Take together, 61 patients were recruited. They experienced preoperative examination, UCMSCs transplantation and follow‐ups.